Revealing asperity-controlled failure patterns in landslides: A case study of Hushuo Expressway, Inner Mongolia - Xing Yuan-hao; Li Chi; Li Shuan-hu; Gao Yu (PLoS ONE, 2025)
This study systematically investigates the failure mechanism of interfacial landslides through experimental validation and engineering applications of interfacial asperity theory. An innovative scaled physical modeling approach was developed, incorporating artificially prefabricated asperities along the sliding interface. Using 3D laser scanning to monitor slope deformation, the physical experiments provide the first direct evidence linking asperity rupture to landslide initiation. The interfacial asperity theory proves particularly effective in analyzing the three recurrent landslides along the Hushuo Expressway (2012–2017), where conventional engineering treatments failed, as all cases exhibited characteristic interfacial sliding mechanisms. The results reveal the nonlinear slip mechanisms of interfacial landslides: the first failure was controlled by asperities at the slope toe, the second by asperities at the slope crest, and the third by structural asperities. Due to post-failure excavation at the site, numerical simulations were employed to reconstruct the failure process, successfully reproducing the controlling effects of different asperity types on landslide evolution. The study also proposes the concept of targeted monitoring and early warning for interfacial landslides.The findings offer a novel theoretical perspective for understanding the progressive failure mechanisms of interfacial landslides and provide critical insights for the design of landslide mitigation measures.